Transactive Criticism on Bridgerton TV Series: Norman N. Holland’s Perspective - Cahya, Eka Sulistia; Siswanti, Sandra Damar (Indonesian literature Program, Faculty of Humanities, Diponegoro University, 2024)
In the new criticism, the reading process is involving both reader and the work. This study aimed to find what makes a work become popular based on readers' responses. By using the Bridgerton first series, this study was analyzed using transactive criticism by Norman N. Holland. According to Holland, in the reading process, there are 4 modalities used by the audience as the step to understand the process of making meaning in Holland’s perspective, there are defense, expectation, fantasy, and transformation. The data was gathered from the comments of the audience in IMDb. The results found that Bridgerton become popular are because of people’s interest in regency era genre, it useful as the pandemic escapism, easy plot, the curiosity of the novel’s reader, the diversity and the high rating. In watching the series, the audience has their own approach and point of view.